Recategorization of Conservation Units in Brazil: A systematic literature review (Research, Society and Development, 2022)
The Brazilian National System of Conservation Units (SNUC) has a wide spectrum of conservationist strategies, so that often the choice of a protected area typology is not adequate to the proposed conservation objectives. The recategorization of a Conservation Unit (CU) is a legal and widely used procedure to resolve conflicts of interest that exist even before the SNUC implementation. This research carried out a Systematic Literature Review (SLR) with the objective of identifying the methods applied in recategorizations and factors that led to the occurrence of this phenomenon in Brazilian CUs. Three bibliographic databases (Research gate, PubMed and Repositório UFSC) were searched, in addition to Google Scholar, obtaining total number of 1,068 articles. The results indicate increase in the number of publications on the theme in the last three years, and that there are twenty methods used in CU recategorization processes in Brazil. A variation of instruments used for recategorization was also identified, and it was found that in most cases, more than one instrument is used, with the implementation of a decree or law being the most used. Several factors are also responsible for recategorization, being territorial conflicts and their overlapping on traditional communities the most relevant.